Mapping Embryogenesis in the Early Phases of Seabass (Lates calcarifer) Eggs on Different Salinities - Djawad, Muhammad Iqbal; Tenriajeng, Muhammad Al Ghiffari; Trijuno, Dody Dharmawan (Marine Science Department Diponegoro University, 2024)
Embryogenesis is a critical stage in the development of fish eggs, as it determines the successful hatching and survival of larvae. Understanding the effects of salinity on embryogenesis is crucial for optimizing hatchery practices and improving the production of fish larvae, such as the seabass. The purpose of this study was to map the stages of embryonic development against various salinities in order to identify the ideal salinity for seabass egg hatching. Eggs from natural spawning in a maintenance bath were used in this investigation. Four containers with salinity treatments (20 ppt, 25 ppt, 30 ppt, and 35 ppt) are used to lay fertilized eggs. The findings demonstrated that, in comparison to 20 ppt and 25 ppt treatments, eggs at 30 ppt and 35 ppt treatments generated faster embryonic development stages. Different incubation salinities have a highly substantial effect on the hatching speed of seabass eggs. Further testing revealed that the eggs hatched in 14 h and 40 min, which had the fastest seabass roe hatching time (35 ppt), and 15 h and 20 min for the 20 ppt salinity treatment. The 35 ppt salinity treatment had the highest hatchability rate (80.67%), while the 20 ppt salinity treatment had the lowest percentage (71.78%). It can be concluded that a salinity of 35 ppt provides a good embryo development response where there are no embryos that fail to develop, have the shortest hatching times of 14 h and 40 min, and produce the highest hatchability of eggs compared to other salinities.